Initial Study of Reduced Graphene Oxide Foams Modified by Mn and Bi as Capacitive Electrode Materials - Olena Okhay; Tao Yang; Alexander Tkach (Nanoenergy Advances)
In a view of application of porous materials in wearable electronics and self-powered systems, reduced graphene oxide (rGO) foams modified by Mn or/and Bi were produced in this study to be used as electrodes for supercapacitors. The hydrothermal method and the freeze-drying processes were used for the preparation of the materials further morphologically, elementally and structurally analyzed. Based on the electrochemical characterization, Bi-modified rGO foam was found to be more a promising material for capacitive electrodes in comparison to the other prepared materials.